Participatory crop breeding reaps benefits for Eritrea - Grando, Stefania (2009)
Few countries are in such acute need of agricultural development as Eritrea,a nation plagued by recurring drought.Its soils are largely parched and unproductive,leading to chronic hunger and poverty for many of its people.Increasing the water productivity of the country ’s most widely grown crops is a priority for government and national researchers. A CPWF project is building on previous work in this field to do just that.Its focus is the Setit-Tekeze River Basin in the western corner of Eritrea.(This is also called the Atbara Basin,Atbara being the name for the Tekeze Riveras it winds through Sudan before joining the Nile). The project,“Improving water productivity of cereals and food legumes in the Atbara River Basin of Eritrea ”,aims to develop and disseminate varieties of barley,wheat,chickpea,lentil,faba bean, cowpea and grass pea that combine drought tolerance with good nutritional characteristics and resistance to diseases and pests.It is also exploring optimum blends for mixed cropping,a risk avoidance strategy that mitigates against the worst effects of drought.